Enhancing the strength-ductility synergy in an iron-based multi-principal element alloy via modulating Mo-rich precipitation - Qiyu Wang; Honghong Su; Yixi Hou; Guoliang Pei; Kerui Yu; Dawei Pang; Luyan Yang; Xiao Wei; Shengcheng Mao; Xiaodong Han (Journal of Materials Research and Technology)
This work proposes a strategy for modulating Mo-rich phase in Fe50Co20Cr15Ni10Mo5 iron-based multi-principal element alloy. Compared with the brittleness problem caused by Mo precipitation strengthening alloy in previous studies, this study realizes the collaborative optimization of strength and ductility through fine regulation of the size and distribution of the precipitates. Through this method, the alloy achieved a high yield strength of 863 MPa with a tensile elongation at break of 27%, benefiting from the synergistic strain hardening induced by the regulation of the precipitation phase. The uniform distribution of precipitation phase at grain boundaries and within grains helps alleviate the premature failure caused by stress concentration at grain boundaries. These findings not only provide valuable guidance for enhancing the role of hard and brittle precipitation phases in alloy systems but also lay a foundation for the structure and performance design of iron-based multi-principal alloys.